2023
DOI: 10.18203/2320-1770.ijrcog20231904
|View full text |Cite
|
Sign up to set email alerts
|

Rate and determinants of low fifth minute Apgar score at the federal medical centre Yenagoa, Bayelsa State, Nigeria

Abstract: Background: About a quarter of neonatal deaths and about 10% of deaths of children under 5 years are due to intrapartum related events reflected as low fifth minute Apgar score. This study is to assess the rate of low fifth minute Apgar score and its determinants at the Federal Medical Centre Yenagoa, Bayelsa State, Nigeria. Methods: A cross-sectional study of births at the Federal Medical Centre Yenagoa between July 2020 and April 2021. Data was collected in real time from parturients’ case notes at delivery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…For example, most of the neonates of group 3 parturients in this study with low fifth-minute APGAR scores were delivered following obstructed labour which is exclusively a complication in unbooked parturients in our setting. Besides, a previous study had identified an unbooked status as one of the determinants of low fifth-minute APGAR scores in FMCY (11).…”
Section: Discussionmentioning
confidence: 96%
“…For example, most of the neonates of group 3 parturients in this study with low fifth-minute APGAR scores were delivered following obstructed labour which is exclusively a complication in unbooked parturients in our setting. Besides, a previous study had identified an unbooked status as one of the determinants of low fifth-minute APGAR scores in FMCY (11).…”
Section: Discussionmentioning
confidence: 96%